The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/agriculture13061130
|View full text |Cite
|
Sign up to set email alerts
|

Design and Motion Process of Air-Sieve Castor Cleaning Device Based on Discrete Element Method

Abstract: In order to improve the cleaning effect of the castor shelling mixture, an air-sieve castor cleaning device was developed. The structure of the cleaning device was optimized by experiment and simulation based on the discrete element method. The results show that the sieving efficiency of the square distribution is 98.23% and the loss rate is 2.39%, both of which are better than the triangular distribution. The sieving efficiency in the condition of a 14 mm sieve hole diameter is 98.23%. For the conditions of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…During harvester operation, the sieve through the shaking plate reciprocating vibration causes material longitudinal and transverse uniform distribution and upward sieve transport, the upper and lower sieves form a sieve box and do reciprocating motion, so that the grains are separated from the material and long impurities, with light impurities in the sieve box, and by means of the airflow are transported backward and discharged out of the machine [13,14]. During this process, the threshing drum and separation concave plate work together to remove the grains.…”
Section: Structure and Working Principle Of Harvester Cleaning Devicementioning
confidence: 99%
“…During harvester operation, the sieve through the shaking plate reciprocating vibration causes material longitudinal and transverse uniform distribution and upward sieve transport, the upper and lower sieves form a sieve box and do reciprocating motion, so that the grains are separated from the material and long impurities, with light impurities in the sieve box, and by means of the airflow are transported backward and discharged out of the machine [13,14]. During this process, the threshing drum and separation concave plate work together to remove the grains.…”
Section: Structure and Working Principle Of Harvester Cleaning Devicementioning
confidence: 99%
“…Different types of holes are used for this purpose. The industrial use of perforated surfaces in separating equipment is typical for technological processes in the following industries: mining and construction [4,5], agricultural and food [6,7], chemical and pharmaceutical [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al developed an air-screen castor cleaning device. Based on the discrete element method, the operating parameters of the cleaning device were optimized, and the parameters of the maximum screening efficiency combination, the minimum loss rate combination, and the best cleaning effect were obtained [14]. Chen et al carried out an experiment using the CFD-DEM coupling method to carry out the numerical simulation of walnut shell-kernel cleaning, and the results showed that in the vertical air duct, the flow rate of the walnut shell would fluctuate around a fixed value, and the settlement rate of the walnut kernels would decrease with the increase in particle concentration and then gradually stabilize [15].…”
Section: Introductionmentioning
confidence: 99%